A behaviour change intervention with lipid‐based nutrient supplements had little impact on young child feeding indicators in rural Kenya. Issue 1 (12th September 2018) - Byrd, Kendra; Dentz, Holly N.; Williams, Anne; Kiprotich, Marion; Pickering, Amy J.; Omondi, Ronald; Kwena, Osborne; Rao, Gouthami; Arnold, Charles D.; Arnold, Benjamin F.; Dewey, Kathryn G.; Colford, John M.; et al.
Abstract: Poor infant and young child feeding (IYCF) practices are associated with linear growth faltering. Our objective was to evaluate the impact of a nutrition and water and sanitation for health intervention on three IYCF indicators—minimum dietary diversity (MDD), minimum meal frequency (MMF), and minimum acceptable diet (MAD) in Kenyan children. Households were randomized into one of eight groups: (a) active control; (b) passive control; (c) water quality (W); (d) sanitation (S); (e) handwashing (H); (f) combined Water, Sanitation, and Handwashing; (g) nutrition (N); and (h) combined WSH + N. In the N and WSH + N arms, community‐based promoters counselled households on optimal IYCF practices, and small‐quantity lipid‐based nutrient supplements (SQ‐LNS) were provided to children 6–24 months of age. Twelve months (Year 1) and 24 months (Year 2) after interventions began, enumerators surveyed mothers to ascertain IYCF practices. We made pairwise comparisons of each intervention arm versus the active control arm using log binomial models. In total, 3, 652 caretakers were surveyed at Year 1 and 4, 987 caretakers at Year 2. Compared with the active control, there were no differences in any of the arms in MDD, MMF, or MAD, aside from an increase in MDD at Year 1 in the nutrition only arm but not in the combined WSH + N arm (N: 68%; WSH + N: 61%; C: 61%; N arm prevalence ratio: 1.13 95% CI [1.01, 1.25]). In this setting, a nutrition behaviour change communication intervention had little impact on IYCF indicators. The provision of SQ‐LNS was not detrimental to current IYCF indicators in the community.